Higher rank aerological risks in coal mines - Sergey V. Balovtsev (Горные науки и технологии, 2022)
The steady trend of complication of mining and geological factors in underground coal mining and at the same time the processes of mining intensification cause growth of dynamic manifestations of natural factors of mining, such as sudden coal and gas outbursts, rock bursts, rock collapses, leading to gas and dust explosions and fires. This requires developing the models of different phenomena manifestation risks, which enable improving the process safety of a mining enterprise. In this study, based on the methodology of aerological risk assessment in coal mines, a structural analysis of aerological risks was carried out. The criteria of hazard of mining-geological and mine engineering factors and vulnerability of schemes and methods of ventilation, ventilation facilities, and main fans were developed. A hierarchical structure of aerological risks of higher ranks was developed. The presented risk structure allows determining the area of superposition of hazards of coal mining and vulnerability of ventilation systems for each mine and its individual facilities, as well as quantifying these areas in the form of aerological risks. The ranges of aerological risk values of higher ranks for super-category mines and mines hazardous by sudden coal and gas outbursts for different ventilation modes were established. The presented methodology enables forecasting and reducing aerological risks in course of designing, operation, liquidation, and conservation of coal mines.